Dendritic silica with carbon dots and gold nanoclusters for dual nanozymes. (22nd January 2020) - Zhao, Lirong; Ren, Xiangling; Zhang, Jing; Zhang, Wei; Chen, Xudong; Meng, Xianwei
Abstract : dSCS-Au NPs were established for dual nanozymes with dendritic silica spheres containing C-dots and Au NCs. Abstract : Many biochemical processes are accomplished by multiple enzymes, so it is important to develop nanocomposite microspheres with multiple enzyme mimetic ability. Here, well-designed nanozyme engineering (termed dSCS-Au NPs) was established for dual nanozymes with dendritic silica spheres (dSs) used as a carrier. The carbon dots (C-dots) were covalently immobilized into the interior surface of amino-terminated dSs, while gold nanoclusters (Au NCs) were linked to the surface of the dSs through activating agents of EDC/NHS. The dSCS-Au NPs exhibited excellent compatibility for two nanozymes, maintaining the superoxide dismutase (SOD)-like activity of C-dots and improving the horseradish peroxidase (HRP)-like activity of Au NCs. In addition, the HRP-like activity of dSCS-Au NPs could be regulated by changing the amount of loading of Au NCs. It has promising applications in biocatalysis with multiple enzyme reactions in the future.